Looking through Three ‘I’s: The Pedagogic Use of Streaming Video - Young, Clive; Asensio, Maria (Proceedings of the International Conference on Networked Learning, 2002)
Although the pedagogic use of film and video has a long history, its widespread use has always been limited by production costs and delivery difficulties. In recent years costs of production have fallen and the web has emerged as a mainstream educational distribution medium. Video itself can be used in many ways: ’talking head’, interviews, video diaries, video labs, simulations, instructional sequences, ’fly on the wall’, video help etc. Through the browser, ’streaming’ video sequences can be linked to slides, text conferencing, whiteboards, video conferencing, shared applications, online assessment and third party web sites. A major element of the JISC/DNER Click and Go Video project is to move beyond the current understanding of video as a purely presentational tool. The seamless combination of digital video with other tools offers an opportunity to experiment with video as a focus for networked learning. However there is an acute lack of pedagogic resources, research and evaluation on the use of video streaming for teaching and learning. The pedagogical challenge faced by teaching staff and practitioners is not only to choose the appropriate streaming technology but also to design meaningful learning events. In this paper we introduce a way to analyse video use through what we have named the Three ’I’s Framework - image, interactivity and integration. This conceptual framework seeks to provide a practical decision tool to help teaching staff and practitioners with the pedagogic design and development of video streaming resources for online learning. Our aim is to provide a way of understanding the role of video as it changes from a presentation tool to a focus for networked learning.